The Role Of IL-4 And IL-8 In The Itiology Of Tinea Versicolor In Group Of Iraqi Patients - AL-Wattar, Wifaq M.; Ghanim, Nahla; Al-Moussawy, Khalida M.; Al-Waiz, Makrum M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Tinea versicolor is a common dermatological problem ,world wide distribution , caused by a dimorphic fungus called Malassezia furfur ,it live normally on skin as a commensal . Many factors play a role in the etiology of TV among these could be the disturbed immune system which may be related to the ability of TV alter the immune system by a process called Immunomodulation leading to subsequent infection. Immuno-inflammatory activity mediated by different cytokines could have a role in the etiology of TV. Objective: To evaluate the serum level of the inflammatory cytokines ,IL-4andIL-8,in patients with TV as compared to immunocompramized patients and healthy groups. Patients and methods: This study enrolled 50 total patients, 15 of them were as patients control group who were immunocompramized with evident skin lesion ,to be compared serologically with 15 patients who had TV and normal immunity, the control group composed of20 healthy volunteers. Using ELISA test technique the following tests were done :detection of IL-4 and IL-8 in the sera of all groups. Results and discussion: The statistical differences in the rate of detectable IL-4 level between TV and healthy control p< 0.001,while the difference was a highly significant between the healthy control and immunocompramized patients with TV,P<0.00338.The difference between two diseased groups was(p< 0.219)which is non significant , when p<0. 05 was considered significant. IL-8 the results of our study showed a significant difference between the healthy control and the patients with tinea versicolor, p-value was( 0.05). In this study there was a nice findings by which the difference between the healthy control and the immunocompramized patients was highly significant as ,p<0.005. Conclusion :The genus Malassezia is an immunological paradox. In some circumstances, it acts as an adjuvant, activates the complement cascade, and elicits both cellular and humoral immune responses in healthy individuals, among which IL8 and IL-4 were notably increased . In contrast, it also seems to have the ability not only to evade the immune system but actually to suppress the response directed against